Benign intranodal thyroid tissue mimicking nodal metastasis in a patient with papillary thyroid carcinoma: A case report. Issue 9 (4th June 2015) - Lee, Yoo Jin; Kim, Dong Wook; Park, Ha Kyoung; Ha, Tae Kwun; Kim, Do Hun; Jung, Soo Jin; Bae, Sang Kyun; Irish, Jonathan
Abstract Background A case of benign intranodal thyroid tissue mimicking nodal metastasis on ultrasound and CT in a patient with papillary thyroid carcinoma has not been reported. Methods The clinical, imaging, and histopathological findings of the patient are presented. A 52‐year‐old woman who underwent ultrasound‐guided fine‐needle aspiration for 2 small, suspicious thyroid nodules in both lobes at a local clinic was referred to our hospital for surgical treatment. Ultrasound‐guided fine‐needle aspiration for a suspicious lymph node in the left upper neck was performed. According to the imaging and cytology results, total thyroidectomy and nodal dissection for both central and left lateral nodes were performed. Results In the histopathology, the lymph node was confirmed as a benign lymph node with intranodal thyroid tissue. Conclusion This case illustrates that benign intranodal thyroid tissue may mimic nodal metastasis on ultrasound or CT in a patient with papillary thyroid carcinoma. © 2015 Wiley Periodicals, Inc. Head Neck 37: E106–E108, 2015